Exploring the sports participation, muscle-strengthening exercise and active commuting with comorbidity of depression and anxiety among Chinese children and adolescents: a cross-sectional study - Feng, Bin; Luo, Fuchen; Chen, Yu; Zhao, Yuhang; Wang, Ping; Bao, Ran (Frontiers in Psychology, 2024)
Prior research has shown that physical activity (PA) is a crucial element for preserving and enhancing health, particularly among children and adolescents, and consistent engagement in PA offers numerous advantages for sustaining typical physical and mental well-being. Purpose Hence, the primary objective of this study was to examine the relationship between sport participation, muscle-strengthening exercise (MSE), and active commuting (AC) in the co-occurrence of depression and anxiety in Chinese children and adolescents. Method This cross-sectional investigation occurred in various cities across the southeastern region of China between March 2021 and October 2021. A convenient sampling method was utilized. We invited children and adolescents to participate in the questionnaire survey. A total of 1,996 participants completed the questionnaires with the endorsement of their parents or guardians under the supervision of schoolteachers and headmasters. Girls comprised 47.5% of the participants, and the average age of participants was 14.8 ± 2.0 years. We conducted a logistic regression analysis, including 95% confidence intervals, to explore the association between sports participation, MSE, AC, and the co-occurrence of depression and anxiety. Results No significant association was observed between weekday active commuting for travelling to and from school and MSE and the comorbidity of depression and anxiety in children and adolescents. A negative association was only detected for those who engaged in muscle-strengthening exercises 4 days a week (OR = 0.540, 95% CI = 0.345–0.845) compared to those who did not partake in such exercises. Conclusion The present study has provided evidence of the connection between sports participation and the co-occurrence of depression and anxiety among Chinese children and adolescents. Sports participation is more likely to help adolescents relieve anxiety and depression than AC, MSE. In forthcoming research, it is imperative to delve deeper into strategies that enhance the impact of sports on the mental well-being of children and young individuals. Furthermore, optimizing the magnitude of this effect may be achievable by focusing on neurobiological, behavioral, and psychosocial mechanisms.